The Effectiveness of Hyaluronic Acid Injection on Rat Tendon Repair Prognosis as a Model in Achilles Tendon Rupture - Adi Mulya; Ismail Bastoni; Erial Bahar (Sriwijaya Journal of Surgery, 2020)
Introduction: Rupture of the Achilles tendon has become an increasingly common case in the last two decades with an incidence of 18% per 100,000 population. The controversy about the best treatment arises because the results are determined by the method of tendon repair and postoperative functional rehabilitation. In recent years, there is a great deal of interest in hyaluronic acid which is found in certain amounts in the soft tissue extracellular matrix and joint fluid. Several experimental studies have shown the application of hyaluronic acid (HA) to heal tendons and stimulate tendon healing and reduce adhesion formation. This research is to find out the effectiveness of injecting hyaluronic acid in behavior changes in mice that have modified Achilles tendon rupture in 21 mice divided into three groups according to their treatment, namely intramuscular HA (IM), Intralesional HA (IL) and NaCl in laboratory animals Sriwijaya University Faculty of Medicine 2019 by seeing changes in behavior every 7 days 3 times. Results: The group with HA-IL treatment had the highest cure success rate, which was 7 (58.3%) good grades, 5 (41.7%) good grades and 2 (100%) very good grades and 5 (33.3%) good and 2 (50%) extraordinary (change behavior 1, 2 and 3, respectively). Then HA-IM 5 (41.7%) Good grades, 7 (58%) Good grades, and 5 (33.3%) and 2 (50%) exceptional grades (change behavior 1, 2 and 3, respectively) and NaCL only have a value of 5 (33.3%) both for behavior change 3. Conclusion: There is a difference in effectiveness between administration of hyaluronic acid and without administration of hyaluronic acid to behavioral changes in repair of the Achilles tendon.